Organized Labour and R&D: Evidence from Italy - Armanda Cetrulo; Valeria Cirillo; Fabio Landini (Global Labor Organization (GLO), 2022)
This paper investigates the impact of firm-level collective bargaining on firms' investment in intangible assets and, specifically R&D. While standard hold-up theories predict a negative effect of organized labour on intangible investments, the inclusion of pay-for-performance schemes in complementary negotiation can actually invert the prediction. Moreover, the industrial relation literature suggests that, in presence of asymmetric power relations, firm-level collective bargaining can allow workers to make their voice heard and induce management to invest in assets that drive competition away from wages, including R&D. We exploit a rich and representative survey on Italian non-agricultural companies conducted by the National Institute for the Analysis of Public Policies (INAPP) to test these predictions. Baseline estimates suggest that the presence of second-level collective bargaining is associated with higher investments in R&D and that power relation is the main mechanism driving this result. These findings are confirmed also in a robustness check where we exploit size contingent legislation governing the creation of employee representative bodies involved in firm-level bargaining in a regression discontinuity design (RDD) framework. The implications for the design of innovation policy are discussed.
Keywords: J50; O32; O33; 330; R&D; Intangibles; Unions; Collective Bargaining; Complementary Negotiation